The Academic Management Strategies in the Digital Era of Secondary Schools under the Secondary Educational Service Area Office Bangkok 2 - Patthanaset, Karntanapa; Thaima, Waraporn (Sripatum Review of Humanities and Social Sciences, 2026)
This research aimed to 1)examine the needs for developing schools into innovative organizations under the Office of Secondary Educational Service Area, Bangkok Area 2, develop guidelines for transforming schools into innovative organizations, and evaluate the approaches for developing schools into innovative organizations. The sample consisted of 450 school administrators and school personnel, selected through stratified random sampling based on school size. The research instruments included a questionnaire with a reliability coefficient of .634 and a focus group discussion record form. The statistics used for data analysis were frequency, percentage, mean, standard deviation, priority needs index (PNI), and content analysis. The research findings revealed that; 1)the priority needs for developing schools into innovative organizations, ranked from the highest to the lowest, were organizational structure, personnel development, an innovation-supportive climate, vision, and the importance of personnel, respectively, 2)the approaches for developing schools into innovative organizations comprised five dimensions, namely organizational structure, personnel development, an innovation-supportive climate, vision, and development, in accordance with the results of the priority needs analysis, and 3) the evaluation of the approaches for developing schools into innovative organizations showed that utility, feasibility, propriety, and accuracy, both overall and in each aspect, were rated at the highest level.